Iyo si Malik - Bayot, Cassey; Ramos, Saturnino Jr
"Toto, 8, and JR, 10, are victims of a recent armed conflict in their city. While playing among the war ruins, they discuss and re-enact their individual war experiences. This story is set in Zamboanga City after the standoff in 2013 between the forces of the Republic of the Philippines and a faction of the Moro National Liberation Front led by Habier Malik.:--Xeph Suarez.